Motivate and select: Relational contracts with persistent types - Radoslawa Nikolowa (Queen Mary University of London, School of Economics and Finance, 2014)
We develop a model of relational contracts with moral hazard and asymmetric persistent information about an employee's type. We find that the form of the optimal contract depends on the job characteristics as well as the distribution of employees' talent. Bonus contracts are more likely to be adopted in complex jobs and when high talent is not too common or too rare. Firms with 'normal' jobs are more likely to adopt termination contracts. In labor market equilibrium, different contracts may be adopted by ex ante identical firms. Hence, we offer an explanation for the co-existence of different employment systems within the same industry.
Keywords: D82; M5; L14; 330; Relational contracts; Job characteristics; Employment systems; Labor market segmentation